2015
DOI: 10.1515/intag-2015-0006
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic model of water vapour adsorption by gluten-free starch

Abstract: A b s t r a c t. This study evaluated the kinetics of water vapour adsorption on the surface of starch molecules derived from wheat. The aim of the study was to determine an equation that would allow estimation of water content in tested material in any timepoint of the adsorption process aimed at settling a balance with the environment. An adsorption isotherm of water vapour on starch granules was drawn. The parameters of the Guggenheim, Anderson, and De Boer equation were determined by characterizing the tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Thus, the static magnetic field resulted in the performance of more work in comparison to the work performed in the absence of the magnetic field impact (Bolton, 1982;Feynman et al, 1974). After the experiment, the examined systems were in states other than the states they were in before the work was done, as determined by changes in the weight of the samples and the saturated salt solutions (Ocieczek, 2013;Ocieczek et al, 2015;Ocieczek and Otremba, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, the static magnetic field resulted in the performance of more work in comparison to the work performed in the absence of the magnetic field impact (Bolton, 1982;Feynman et al, 1974). After the experiment, the examined systems were in states other than the states they were in before the work was done, as determined by changes in the weight of the samples and the saturated salt solutions (Ocieczek, 2013;Ocieczek et al, 2015;Ocieczek and Otremba, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The final step of the research consisted of a comparison of the sorption range in the control conditions and when stimulated with a static magnetic field. Differences in the equilibrium state were determined by comparing the water content in the examined samples after eight days of storage, which was assumed as a satisfactory period for reaching a state of dynamic equilibrium by this system (Ocieczek et al, 2015). A statistical evaluation of the differences demonstrated that the range of adsorption, expressed as an increase in the weight of the samples after eight days of storage, was higher in the magnetic field condition (tGC/GF/NaCl = 14.0608; tSC/SF/NaCl = 12.311; t0,001 = 8.61).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Surface phenomena affect both the kinetics and intensity (kinetics + range) of many physical, physicochemical, chemical, biochemical, and microbiological processes. These, in turn, determine the storage stability of food (Rahman 2006, Ocieczek et al 2015. One natural and commonly occurring phenomenon is the drying of biological matter, the essence of which is water desorption from its surface to the environment.…”
Section: Introductionmentioning
confidence: 99%